5 Year Outcomes of Patients With Aortic Structural Valve Deterioration Treated With Transcatheter Valve in Valve – A Single Center Prospective Registry - Schamroth Pravda, Nili; Kornowski, Ran; Levi, Amos; Witberg, Guy; Landes, Uri; Perl, Leor; Shapira, Yaron; Orvin, Katia; Mishaev, Raffael; Talmor Barkan, Yeela; Hamdan, Ashraf; Sharoni, Ram; et al. (Frontiers in Cardiovascular Medicine, 2021)
The Valve-in-Valve (ViV) technique is an established alternative for the treatment of structural bioprosthetic valve deterioration (SVD). Data describing the intermediate term follow up of patients treated with this approach is scarce. We report on our intermediate-term outcomes of patients with SVD in the Aortic position treated with ViV. Included were patients with symptomatic SVD in the aortic position valve who were treated by Valve in valve transcatheter aortic valve implantation (ViV-TAVI) during the years 2010-2019 in our center. Three main outcomes were examined during the follow up period: NYHA functional class, ViV-TAVI hemodynamic per echocardiography, and mortality. Our cohort consisted of 85 patients (mean age 78.8 ± 8.9 years). The indications for aortic ViV were: SVD isolated aortic stenosis in 37.6%, SVD isolated aortic regurgitation in 42.2% and combined valve pathology in 20.0%. Self-expandable and balloon-expandable devices were used in 73 (85.9%) and 12 (14.1%), respectively. Average follow up was 3.7 ± 2.4 years. 95 and 91% of patients were in NYHA functional class I/II at 1 and 5 year follow up respectively. At one year, the mean trans-aortic valve pressure was 15 ± 9 mmHg and rates of ≥ moderate aortic regurgitation were 3.7%. Mortality at one year was 8.6% (95% CI 2.3–14.4) and 31% (95% CI 16.5–42.5) at 5 years. ViV in the aortic position offers an effective and durable treatment option for patient with SVD, with low rates of all-cause mortality, excellent hemodynamic and improved functional capacity at intermediate follow up.